PENANGGULANGAN KRISIS LEGITIMASI HUKUM MELALUI HUKUM PROGRESIF - Agus Muhammad Septiana (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Practice of law enforcement in Indonesia are degraded to the lowest point in NKRI history. Corruption seems to be a common activity performed by public officials as well as communal done, whether they are sporadic and are structured. Even in some cases, corruption is legalized by the state policy. Law loses its legitimacy as a tool of social engineering. Provide further explanation of how to break the deadlock of law inforcement by Progressive Law in Indonesia, and simultaneously address the crisis of legitimacy of law in Indonesia. That the law can still be accepted by society as an institution where justice must be found, then the law must always be prepared to move in accordance with the changes taking place in society. To implement the action level should be preceded by agreement on the law enforcement component of law enforcement that